The Effect of Environmental Education Learning for Enhancing Rivers Management in the Northeast of Thailand Using Community-Based Learning - Prayoon Wongchantra,; Suparat Ongon,; Likhit Junkaew,; Kannika Sookngam,; Uraiwan Praimee,; Surasak Kaeongam,; Thongchai Pronyusri,; Phanadda Ritsumdaeng,; Kuantean Wongchantra, (Journal of Educational Issues, 2024)
Community-based learning is a strategy or model of learning management that integrates curricular content into the community using work based learning to encourage learners to learn from real-life situations in the community under the participation of teachers, learners and people in the community. The purposes of this research were to develop environmental education learning plans for enhancing rivers management in the Northeast of Thailand using community-based learning as effective and effective, to study and compare knowledge, attitude and environmental ethics for enhancing rivers management in the northeast before and after study and to compare knowledge, attitude and environmental ethics for enhancing rivers management in the Northeast of students with different gender. The sample used in the study were 50 the third year undergraduate students in Environmental Education program, Faculty of Environment and Resource Studies, Mahasarakham University, which was derived by purposive sampling. The research tools were the environmental education learning plans for enhancing rivers management in the Northeast of Thailand using community-based learning, knowledge test, attitude test and environmental ethics test. The statistics used for data analysis were frequency, percentage, mean, standard deviation and hypothesis testing using Paired t-test and One-Way ANOVA. The results of the research showed that: 1) The environmental education learning plans for enhancing rivers management in the Northeast of Thailand using community-based learning were the efficiency of 81.08/85.43, the efficiency index was a value of 0.7709, it showed that the students have increased knowledge and resulted in the students progressing from their studies accounted 77.09%; 2) The students had average score of the knowledge, attitude and environmental ethics in the posttest higher than the pretest statistical significance (p < .05); 3) There was statistically significant different of score of knowledge, attitude and environmental ethics of students with different gender (p < .05).